A dairy-based beverage development by alpha-lactalbumin/beta-lactoglobulin ratio adjustment for dysphagia patients - Wei, Ting (Kansas State University, 2014)
People who suffer from swallowing disorders are diagnosed with dyphasgia. The beverage for the dyphagia patients should have the apparent viscosity in the range of nectar-like (51 to 350 mPa•s) or honey-like (351 to 1750 mPa•s). Due to the swallowing problems, dysphagia patients usually consume beverages slowly. Thus, the apparent viscosity of beverage for such patients should be high enough to be in the suitable range during the entire time of consumption. Three ratios of α-lactalbumin (α-la)/β-lactoglobulin (β-lg) (3:8, 1:1 and 8:3) were used to prepare the milk systems. These ratio adjusted milk systems were either processed at 70, 80, and 90ºC for 30 min or at 25ºC, and cooled to 25 ± 1ºC. After the process was completed, the milk systems were set quiescently 120 min at 25 ±1ºC. Physical and chemical properties were assessed at various time. For the milk systems at 0 min, the apparent viscosity increased in all 90°C processed-samples, and the increase was in the order of 8:3 (15.96%), 1:1 (6.38%) and 3:8 (2.11%) compared with the 25ºC samples at each ratio. When the milk systems set for 120 min, apparent viscosity increased slightly by 3.7%. The maximum apparent viscosity was 2.18 mPa•s, which was less than nectar-like. Therefore, xanthan gum was added at 0.15 w/w % to enhance rheological properties of the milk systems. α-La/β-lg ratio adjusted milk systems either with or without xanthan gum were prepared, and processed at 90ºC or 25ºC, and cooled to 25 ± 1ºC. Apparent viscosity increased by 48.61 and 89.61% in 3:8 and 8:3 milk systems, respectively for those at 0.15% xanthan gum concentration and processed at 90ºC compared with at 25ºC. Apparent viscosity of 8:3 milk systems at xanthan gum concentration of 0.15% processed at 90°C was 58.7 ± 2.12 mPa•s which was within the nectar-like range. When the samples were set for 120 min, no changes were found in the apparent viscosity of the milk systems. If the rheological properties of the milk systems can be controlled by ingredients interactions, this can be used to develop nutritious products with different forms for dysphagia patients.
Keywords: Casein micelles; Denatured whey proteins; alpha-lactalbumin; β-lactoglobulin; Physical properties; Food Science (0359)